Africa is the Future : un film de Nicolas Premier : aux confluences des expériences africaines et afrodescendantes qui transcendent l’espace-temps – ou comment guérir de traumatismes répétés ? - Bracmort, Cécilia (RACAR : Revue d'art canadienne / Canadian Art Review)

(untitled) (UAAC-AAUC (University Art Association of Canada | Association d'art des universités du Canada), 2022)
This article offers an analysis of the film Africa is the Future by the French-Congolese artist Nicolas Premier. Mixing historical elements and popular culture by assembling and reassembling archival material ranging from literary and cinematic references to television shows and advertising, Africa is the Future highlights the plurality and complexity of the pan-African Black experience. With this work, Premier demonstrates the ongoing connection between the African continent and its diaspora as well as the importance of connecting these different spaces, temporalities, and communities in order to begin a process of healing the many separations and breaks that have occurred over the past centuries. Offering a history of the project as well as a reading of this poetic and compelling work, this text elucidates Premier’s focus on ritual, community, and healing.